The implementation of LKS based on the concept attainment model to improving student's analytical thinking ability - Raddina Aprilia Putri; Yunin Hidayati; Irsad Rosidi; Wiwin Puspita Hadi (JURNAL BIOEDUKATIKA, 2020)
Concept attainment models are learning models that can bring students to analytical thinking, and their phases are indicators of analytical thinking. This study aims to determine the application of student worksheets based on the concept of attainment models on the topic of the interaction of living things with their environment to improve analytical thinking skills. This research is a quasi-experimental study with One Group Pretest-Posttest research design. The sample is students of class VII-G of SMP N 1 Arosbaya, sampling technique with a purposive sampling technique. Data collection techniques using analytical thinking skills tests, and then the test results were analyzed statistically. The results showed that the N-Gain value was 0.46 (moderate). Paired t-test shows the significance value of 0.000, if sig <0.05 then H0 is rejected (-tcount < ttable <tcount = -14.020 <2.052 <14.020). Based on the N-Gain Score and the comparison of the critical values of ttable and tcount, there is an increase in students' analytical thinking skills after learning using student worksheets based on the concept attainment models. Analytical thinking skills will facilitate students in the process of solving problems and drawing conclusions.